Glomerular expression of matrix metalloproteinases in AL-amyloidosis and association with renal function at the time of kidney biopsy - Charitaki, E.; Kastritis, E.; Petraki, C.; Liapis, K.; Adamidis, K.; Apostolou, T.; Christodoulidou, C.; Nikolopoulou, N.; Terpos, E.; Nakopoulou, L.; Dimopoulos, M.A. (Clinical Nephrology, 2016)
Background: Matrix metalloproteinases (MMPs) have been implicated in the pathophysiology of various renal diseases, however, there are limited data regarding their role in renal AL-amyloidosis. In the present study, we evaluated the glomerular expression of MMPs in renal-biopsy specimens containing AL-amyloid deposits. We also examined the association of MMPs with renal function at the time of diagnostic renal biopsy. Methods: We performed immunohistochemistry with monoclonal antibodies against MMP-1, MMP-2, MMP-3, MMP-9, and TIMP-1 in 19 kidney-biopsy specimens with AL-amyloidosis and 8 specimens from normal kidney tissue. We used clinical data of the patients at the time of kidney biopsy to evaluate the association between MMP expression and renal function. Results: We found increased MMP-1 and MMP-3 expression within the amyloid deposits and adjacent tissues in > 50% of the amyloid-positive biopsies, whereas MMP-1 and MMP-3 were negative in control samples. In contrast, we found no significant glomerular MMP-2 and TIMP-1 expression in amyloid-containing or normal kidneys. MMP-9 expression was found in the glomerular basement membrane equally in AL-amyloidosis and control specimens. The presence of MMP-1 and MMP-3 in the glomeruli of patients with AL-amyloidosis correlated with worse renal function at the time of kidney biopsy. Conclusion: The findings of this study show increased glomerular expression of MMP-1 and MMP-3 in patients with AL-amyloidosis which is associated with worse renal function at the time of the kidney biopsy. Our results suggest an important role for MMP-1 and MMP-3 in the pathogenesis of renal damage in AL-amyloidosis. © 2016 Dustri-Verlag Dr. K. Feistle.
Keywords: AL-amyloidosis; Matrix metalloproteinases; Renal amyloidosis